Issues In Supply Chain Management For DHL Exel - Govuindasamy, Gayathri (2009)
The purpose of this study divide into 3 factors. Firstly, the study was document facet and overall supply chain management performances in DESC. Secondly, the results of this research were used to the variability of the framework. Lastly, the study was to investigate whether a communication and relationship between management-employee and management-customers existed and gained overall satisfaction.